Characteristics of Stable Isotope Compositions (δ18O and δ2H) of Surface Water in Bengkulu City - B.N. Zega; S. He; A.M. Lubis (Atom Indonesia, 2020)
Indonesia as an archipelagic country has a unique location and topography, and the El Niño-Southern Oscillation (ENSO) is observed in this region, resulting in complex weather and climate variability. As a result, Indonesia including Bengkulu experiences regular natural disasters. Stable isotopes (δ18O and δ2H) have been used as natural tracers in solving water resources and water-related problems. The aim of this research is to investigate the variations of stable isotopes in Bengkulu City from three locations, namely Serut and Hitam Rivers and the Universitas Bengkulu (UNIB) lake, and to understand the hydrological processes in Bengkulu City. In this research, samples of surface water from Serut and Hitam Rivers and UNIB Lake in Bengkulu City were collected over five months between December 2018 and April 2019. Stable isotope compositions of these water samples were examined to understand the local hydrological processes. The result shows that the water samples are generally situated at the right side of Local Meteoric Water Line (LMWL) in δ18O and δ2H plot, indicating that water samples are more enriched in 18O and 2H as compared with the rainwater due to fractionation processes. The surface water samples define a local evaporation line with a slope of 6.536 while the LMWL has a slope of 7.848. This result indicates a significant evaporation effect on water bodies. Moreover, the slope of the regression line in all water samples was lower than the LMWL, in order of Serut River (7.696) > Hitam River (6.851) > UNIB Lake (6.436), indicating that UNIB Lake experienced more significant evaporation than river waters, resulting in enrichment in heavy isotopes. Serut River, one of largest river in Bengkulu City, which also plays an important role in flooding in Bengkulu City, has a regression equation similar to the regression line of rainwater (LMWL). It may be indicated that surface water from Serut River is strongly influenced by rainwater. Consequently, high amount of rainfall can affect the water level of Serut River, and can be associated with flooding. Therefore,   long-term monitoring of stable isotopes is very important in the future to provide the pattern of changes in isotopic variation, particularly during flood and drought events as climate-disaster mitigation effort.